2021
DOI: 10.1002/cben.202000035
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalysis of Second Generation Oil for Biodiesel Production: A Review

Abstract: The demand for cleaner fuels has been on the rise lately, prompting researchers to explore alternative cleaner technologies to meet the growing demand. This has led to the introduction of renewable fuels such as bioethanol and biodiesel. Depending on the feedstock employed for production, renewable fuels can be divided into first, second, and third generation. Reliance on first generation biofuel feedstocks has led to inherent competition between foods versus fuels in the society in the last decade. Further te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Africa has abundant sources of WCO that can be converted to biodiesel to meet increasing energy needs. Studies at universities in Africa, particularly in Nigeria, have shown that efficient methods for producing high-quality biodiesel can be produced from waste oils from hotels, cafeterias and households [27][28]. African researchers are at the forefront of exploring the use of WCO as a viable feedstock for biodiesel production, driven by continent's growing interest in sustainable energy solutions and environmental protection.…”
Section: Waste Cooking Oils: An Abundant Resourcementioning
confidence: 99%
“…Africa has abundant sources of WCO that can be converted to biodiesel to meet increasing energy needs. Studies at universities in Africa, particularly in Nigeria, have shown that efficient methods for producing high-quality biodiesel can be produced from waste oils from hotels, cafeterias and households [27][28]. African researchers are at the forefront of exploring the use of WCO as a viable feedstock for biodiesel production, driven by continent's growing interest in sustainable energy solutions and environmental protection.…”
Section: Waste Cooking Oils: An Abundant Resourcementioning
confidence: 99%
“…In the biofuels conversions processes, homogeneous and heterogeneous catalysts are two of the most popular groups of catalysts in appplications. 185,186 Contrary to homogeneous catalysts, which are described as having a sluggish reaction rate and being sensitive to the amount of free fatty acids in the oil, [187][188][189][190] heterogeneous catalysts have been demonstrated to have a long reaction time and high temperature, along with the production of undesired by-products. 191,192 However, it has been demonstrated that calcium oxide has superior catalytic qualities compared to other heterogeneous catalysts, including being effective, reusable, non-toxic, and most cost-effective due to its ease of availability.…”
Section: Operating Conditionsmentioning
confidence: 99%
“…Feedstock for second-generation lignocellulosic biofuels primarily consists of form of biomass that are unfit for human consumption, hence, it does not compete with th production of food. Potential raw materials for second-generation biofuels consist of: ( crop residue biomass; (2) non-food energy crops; (3) Jatropha; (4) wood residues; and ( bacteria [7,22,34,[43][44][45][46]. In addition to its direct use, second-generation biofuel can also be mixed with petroleumbased fuels in existing engines or used in slightly adapted vehicles with a compatible engine (e.g., vehicles for DME) [33].…”
Section: Feedstock For Second-generation Lignocellulosic Biofuelsmentioning
confidence: 99%